The structure and optical dispersion of the refractive index of tellurite glass - Capanema, W. A. [UNESP]; Yukimitu, K. [UNESP]; Moraes, João Carlos Silos [UNESP]; Santos, F. A. [UNESP]; Figueiredo, M. S. [UNESP]; Sidel, S. M. [UNESP]; Reynoso, V. C. S. [UNESP]; Sakai, O. A.; Medina, A. N. (Elsevier B.V., 2011)
The structure and optical properties of a 80TeO(2)-(20-x)Li(2)O-xTiO(2) glass system where x = 0, 5, 10, and 15 mol% has been investigated using FTIR spectroscopy and Brewster angle measurements. The sample preparation, linear refractive index and density measurements, and infrared spectroscopic analysis are described. The refractive index and density of the studied tellurite glass samples increase when the amount of Ti in the glass is increased. The dispersion of the phase refractive index was analyzed using Wemple's model. The dispersion energy E(d) is significantly affected by the addition of Ti to TeO(2)-based glass. The analysis of FTIR spectra indicate a Te coordination change that is in agreement with the increase of the Te coordination number determined from dispersion data using Wemple's equation. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Tellurite glass; Optical dispersion; Infrared spectroscopy; Refractive index